Unlucky punches: the vulnerability-stress model for the development of impulse control disorders in Parkinson’s disease - Hendrik Theis; Catharina Probst; Pierre-Olivier Fernagut; Thilo van Eimeren (npj Parkinson's Disease, 2021)
Abstract Impulse-control disorders are commonly observed during dopamine-replacement therapy in Parkinson’s disease, but the majority of patients seems “immune” to this side effect. Epidemiological evidence suggests that a major risk factor may be a specific difference in the layout of the dopaminergic-reinforcement system, of which the ventral striatum is a central player. A series of imaging studies of the dopaminergic system point toward a presynaptic reduction of dopamine-reuptake transporter density and dopamine synthesis capacity. Here, we review current evidence for a vulnerability-stress model in which a relative reduction of dopaminergic projections to the ventral striatum and concomitant sensitization of postsynaptic neurons represent a predisposing (hypodopaminergic) vulnerability. Stress (hyperdopaminergic) is delivered when dopamine replacement therapy leads to a relative overdosing of the already-sensitized ventral striatum. These alterations are consistent with consecutive changes in reinforcement mechanisms, which stimulate learning from reward and impede learning from punishment, thereby fostering the development of impulse-control disorders. This vulnerability-stress model might also provide important insights into the development of addictions in the non-Parkinsonian population.